2019
DOI: 10.1186/s12955-019-1157-2
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in undergraduate women using any contraceptive

Abstract: Objective The aim of this research was to assess university students’ health-related quality of life whether they use some contraceptive method or not. Methods This research is a cross-sectional study. Female participants who studied a degree in health at the University of Seville (Spain) were recruited. Respondents completed a demographic questionnaire and health-related quality of life was measured with validated instrument SEC-QoL (Sociedad Española de Contracepción-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Conversely, contraception has also been linked to improving women's quality of life in several domains [15,19,20], and our findings support research showing that positive side effects of contraception include improved sexual satisfaction through reduced anxiety and reduced bleeding [21]. This highlights the importance of finding the right method of contraception that suits the needs of the individual in the context of their wider lives and goals.…”
Section: Results In the Context Of What Is Knownsupporting
confidence: 80%
“…Conversely, contraception has also been linked to improving women's quality of life in several domains [15,19,20], and our findings support research showing that positive side effects of contraception include improved sexual satisfaction through reduced anxiety and reduced bleeding [21]. This highlights the importance of finding the right method of contraception that suits the needs of the individual in the context of their wider lives and goals.…”
Section: Results In the Context Of What Is Knownsupporting
confidence: 80%
“…In an industry-sponsored study of premenopausal women initiating a specific OCP containing 30 mcg ethinyl estradiol and progesterone, participants had improved mental component summary scales of the SF-12, another general health-related quality of life instrument, after two months of using this OCP compared to their baseline scores before initiating this OCP, in addition to reduction of premenstrual symptoms [23] . A cross-sectional study of university students in Spain using the SEC-QOL, a Spanish contraception-specific quality of life instrument, found that women using contraception had higher SEC-QOL scores and that women using hormonal contraception had higher SEC-QOL scores than women using non-hormonal contraception [24] .…”
Section: Discussionmentioning
confidence: 99%
“…58 This was same as reported by Leorns. 57 According to Zethraeus et al oral contraceptives had no negative effect on overall sexual function. 59 Leorn also reported in his study that women who used contraception methods had lower menstrual scores and higher sexual health-related QoL.…”
Section: Quality Of Life and The Use Of Ocsmentioning
confidence: 97%
“…This is opposed to many studies that reported an improvement after the use of pills. 57 Zhao in his studies among rural Chinese women, reported a significant improvement in QOL from combined oral contraceptive (COC) use mostly due to the hormonal non contraceptive benefits. 58 Impact of OC on the sexual domain of QoL have not been consistent among various reports.…”
Section: Quality Of Life and The Use Of Ocsmentioning
confidence: 99%